Profil psoriasis di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari 2013 – Desember 2015 - Boham, Michelle P.; Suling, Pieter L.; Pandaleke, Herry E.J. (e-CliniC, 2016)
Abstract: Psoriasis is a skin disease that belongs to erythrosquamous dermatosis, characterized by erythema and scaling. Psoriasis are usually localized on the elbows, knees, and scalp, however, it can spread to almost all areas of the body. Its causes are still not known for certain but it is suspected that this disease is related to genetic, immunological, and environmental factors. This study was aimed to obtain the profile of psoriasis in the Dermatovenereology Clinic of Prof. Dr. R. D. Kandou Hospital Manado from January 2013 to December 2015. This was a retrospective descriptive study using the medical record data. The results showed that of 3573 new cases of skin diseases, 188 were classified as psoriasis (5.26%). The majority of psoriasis cases were males (57.98%), aged 45-64 years (50.53%), occupation as housewife (16.48%), and diagnosed as psoriasis vulgaris (80.85%). Psoriasis typically found in the head, body, and extremities was found in 73.94% of cases. The most common type of treatment was a combination of topical corticosteroid and oral antihistamine (68.62%).Keywords: psoriasis, erythrosquamous dermatosis Abstrak: Psoriasis merupakan salah satu jenis penyakit kulit yang termasuk dalam golongan dermatosis eritroskuamosa, ditandai dengan adanya eritema dan skuama. Letak psoriasis dapat terlokalisir, misalnya pada siku, lutut, kulit kepala, atau menyerang hampir 100% luas tubuhnya. Penyebabnya belum diketahui secara pasti, namun diduga penyakit ini di[engaruhi oleh faktor genetik, imunologik, dan lingkungan. Penelitian ini bertujuan untuk mendapatkan profil psoriasis di RSUP Prof. Dr. R. D. Kandou Manado periode Januari 2013 – Desember 2015. Jenis penelitian ialah deskriptif retrospektif menggunakan data rekam medik. Hasil penelitian menunjukkan dari 3573 kunjungan baru penyakit kulit, terdapat 188 kasus baru psoriasis (5,26%). Mayoritas kasus ialah laki-laki (57,98%), usia 45-64 tahun (50,53%), pekerjaan tersering ibu rumah tangga (16,48%), dan diagnosis sebagai psoriasis vulgaris (80,85%). Psoriasis paling banyak mengenai kepala, badan, dan ekstremitas (73,94%). Terapi yang paling sering digunakan ialah kombinasi kortikosteroid topikal dan antihistamin oral (68,62%). Kata kunci: psoriasis, dermatosis eritroskuamosa